Cortical thickness in the right medial frontal gyrus predicts planning performance in healthy children and adolescents - Kollndorfer, Kathrin; Novak, Astrid; Nenning, Karl-Heinz; Fischmeister, Florian Ph S.; Seidl, Rainer; Langs, Georg; Kasprian, Gregor; Prayer, Daniela; Bartha-Doering, Lisa (Frontiers in Psychology, 2023)
The ability to plan is an important part of the set of the cognitive skills called "executive functions".To be able to plan actions in advance is of great importance in everyday life and constitutes one of the major key features for academic as well as economic success. The present study aimed to investigate the neuroanatomical correlates of planning in normally developing children, as measured by the cortical thickness of the prefrontal cortex. Eighteen healthy children and adolescents underwent structural MRI examinations and the Tower of London (ToL) task. A multiple regression analysis revealed that the cortical thickness of the right caudal middle frontal gyrus (cMFG) was a significant predictor of planning performance. Neither the cortical thickness of any other prefrontal area nor gender were significantly associated with performance in the ToL task. The results of the present exploratory study suggest that the cortical thickness of the right, but not the left cMFG, is positively correlated with performance in the ToL task. We, therefore, conclude that increased cortical thickness may be more beneficial for higher-order processes, such as information integration, than for lower-order processes, such as the analysis of external information.